Analisis Peran Pengendalian Internal dalam Mencegah Kecurangan dan Meningkatkan Efektivitas Organisasi: Studi Pustaka - Sarah Putri Nuryanti1*, Putri Nuryanti1; Neza Miftahuljannah; Ela Puspita; Febi Ayu Sonia; Azka Fatilla; Dhaifina Nabila Nasution (ICONS: Islamic Economics Journal, 2025)
Fraud is a critical issue that threatens the effectiveness and sustainability of organizations. Internal control plays a key role in fraud prevention and supports the establishment of an accountable governance system. This study aims to analyze the role of internal control in preventing fraud and enhancing organizational effectiveness through a literature review approach. The research method is descriptive qualitative, using thematic analysis of 24 journal articles and 4 relevant academic books. The results indicate that effective internal control can reduce fraud risk through structured supervision, transparent reporting, and proper segregation of duties. The presence of internal and external audits reinforces the control system through independent validation and layered oversight. Furthermore, ethical organizational culture, individual morality, and the use of information technology significantly influence the effectiveness of internal control. The study concludes that an integrated, ethical, and technology-supported internal control system is essential for building a resilient and accountable organization.